A retrospective analysis for investigating the relationship between FIGO stage IVA/IVB and cytoreductive surgery with prognosis in epithelial ovarian cancer - Liu, Hong; Luo, Min; Peng, Chunrong; Huang, Jianmei; Wang, Dengfeng; Huang, Jianming; Zhang, Guonan (Frontiers in Oncology, 2023)
Objective: To investigate the effect of primary debulking surgery (PDS), NACT followed by interval debulking surgery (NACT-IDS), and chemotherapy alone on the prognosis of FIGO stage IV epithelial ovarian cancer (EOC) with different metastatic patterns. Methods: We retrospectively analyzed 133 cases of FIGO stage IV EOC with pleural effusion (stage IVA), parenchymal metastases (stage IVB), or extra-abdominal lymph node metastases (stage IVB) at our Hospital between January 2014 and July 2021. Results: Among 133 cases with stage IV disease, 16.5% (n=22) presented with pleural effusion, 46.6% (n=62) with parenchymal metastases, and 36.9% (n=49) with extra-abdominal lymph node metastases. Regardless of the metastatic patterns, the 90.2% (n=120) of cases who underwent PDS/NACT-IDS exhibited a significantly superior overall survival (OS) compared to the 9.8% cases (n=13) who received chemotherapy alone (32 vs 17 months, p=0.000). The cohort was further stratified into 58 cases (48.3%) with R0, 41 cases (34.2%) with R1, and 21 cases (17.5%) with R2. The median OS of cases with R0 was significantly better than that of cases with R1/R2 (74 vs 27 months, p=0.000). There was no significant difference in median OS between PDS and NACT-IDS (43 vs 31 months, p=0.676), as well as between FIGO IVA and IVB (35 vs 31 months, p=0.582). Additionally, the metastatic patterns and the number of neoadjuvant chemotherapy cycles (≤4 or >4) did not demonstrate any prognostic significance for median OS (p=0.820 and 33 vs 26 months, p=0.280, respectively). Conclusion: Regardless of FIGO IVA and IVB stages or metastatic patterns, patients diagnosed with stage IV EOC may benefit from cytoreductive surgery with abdominal R0, compared with chemotherapy alone.